A high conductivity carbon fiber composite bipolar plate base material and preparation method thereof
The combination of polyaniline coating oxidation treatment carbon fibers with modified resins and natural flake graphite solves the shortcomings of existing bipolar plate materials in terms of corrosion resistance, conductivity and strength, and achieves high conductivity and low cost carbon fibers Composite bipolar plates meet the high-performance needs of new energy vehicles.
Patent Information
- Application Number
- CN202310586350.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-23
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-05-23
AI Technical Summary
Existing bipolar plate materials such as graphite and metal bipolar plates have shortcomings in corrosion resistance, conductivity and strength, which is difficult to meet the demand for high-performance bipolar plates of new energy vehicles.
Using polyaniline-coated oxidation treatment carbon fibers combined with modified resins and natural scale graphite to prepare high-conductivity carbon fiber composite bipolar plate base material, and improve the conductivity of bipolar plates through liquid phase oxidation and cold pressing molding process. Performance and mechanical properties.
The ultra-thin, high conductivity, low hydrogen permeability, excellent corrosion resistance and low production energy consumption of bipolar plates are achieved, reducing production costs and improving the overall performance of bipolar plates.
Smart Images

Figure CN116694059B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cells and relates to a composite bipolar plate base material and a preparation method thereof. Background Art
[0002] Nowadays, new energy vehicles are developing rapidly and have broad development prospects. As an important part of automobile components and the key core of fuel cells, bipolar plates play an important role. In fuel cells, bipolar plates account for more than 60% of the total mass of fuel cells and play an irreplaceable role. They can not only evenly distribute the reaction gas to the electrodes, but also have the function of quickly conducting current and connecting the single cells in series to accelerate the conductivity rate. In the development and utilization of bipolar plates, graphite bipolar plates and metal bipolar plates were commonly used in the past. Graphite is the earliest developed bipolar plate material, but bipolar plates made of graphite have the disadvantages of large material porosity, poor mechanical properties, general heat resistance, and general gas barrier properties. In order to solve this pain point, metal materials with excellent mechanical properties have been widely studied. However, metal bipolar plates are easily corroded and prone to catalyst poisoning, surface passivation and other problems. At present, only new alloy materials or surface treatment methods such as coatings can be used to solve the corrosion resistance problem. The polymer composite bipolar plate combines the advantages of the above two types of plates and has become an important trend for researchers to study bipolar plates. People are gradually using more cost-effective composite materials to reduce the production cost of bipolar plates and improve their performance. The important role of bipolar plates has led us to have higher requirements for the air tightness, corrosion resistance, conductivity, strength and hardness of bipolar plates. In view of the above situation that metal bipolar plates and graphite bipolar plates are not strong enough and have insufficient conductivity, a carbon fiber composite bipolar plate base material with both ultra-thinness and high conductivity is needed to improve the performance of bipolar plates. Summary of the invention
[0003] The present invention aims to overcome the above-mentioned existing problems and provide a high-conductivity carbon fiber composite bipolar plate base material for preparing ultra-thin high-conductivity carbon fiber composite bipolar plates. The carbon fiber composite bipolar plate has the advantages of low hydrogen permeability, low thickness, high strength, excellent corrosion resistance, low resistivity, low production energy consumption, and high efficiency. On the other hand, the present invention also provides the above-mentioned high-conductivity carbon fiber composite bipolar plate base material and a method for preparing an ultra-thin high-conductivity carbon fiber composite bipolar plate.
[0004] The present invention solves the above problems through the following technical solutions:
[0005] The raw materials for preparing the high-conductivity carbon fiber composite bipolar plate base material provided by the present invention include the following components calculated by mass: 6.8-7.2 parts of conductive filler, 18.5-23.8 parts of modified resin, 68-72 parts of natural flake graphite, and 1.4-3 parts of curing agent; the conductive filler includes polyaniline-coated oxidized carbon fiber.
[0006] Furthermore, the preparation method of the polyaniline-coated oxidized carbon fiber comprises the following steps: uniformly mixing hydrochloric acid (1-2 mol / L), a polyaniline solution (0.5-1 mol / L) and oxidized carbon fiber and heating, gradually dropping an oxidizing solution a, and stopping the reaction when the reaction time is at least 6 hours and the color of the reaction system turns blue-black, thereby obtaining a polyaniline-coated oxidized carbon fiber;
[0007] The mass ratio of the hydrochloric acid, the polyaniline solution, the oxidation-treated carbon fiber and the oxidizing solution a is 0.3:0.5-1:6.8-7.4:0.2-0.6.
[0008] Specifically, the oxidation treatment method in the oxidation-treated carbon fiber includes at least one of liquid phase oxidation, gas phase oxidation, and electrochemical anodization; preferably, the liquid phase oxidation method. The liquid phase oxidation method for treating carbon fiber includes the following steps: adding an oxidizing solution a' to the carbon fiber, heating it to cause a violent redox reaction, and obtaining the carbon fiber after liquid phase oxidation treatment after cooling.
[0009] Wherein, the oxidizing solution a' comprises at least one of potassium chlorate solution, periodic acid solution, concentrated nitric acid, concentrated sulfuric acid, potassium permanganate solution, acidified potassium dichromate solution, sodium hypochlorite solution, hydrogen peroxide solution and potassium persulfate solution;
[0010] The mass ratio of the oxidizing solution a' to the carbon fiber is 0.3-0.6:4; the concentration of the oxidizing solution a' is 1-2 mol / L.
[0011] Furthermore, the modified resin includes at least one of acrylate-modified waterborne polyurethane and modified epoxy-type vinyl ester resin, preferably modified epoxy-type vinyl ester resin.
[0012] Specifically, the preparation method of the acrylate-modified waterborne polyurethane comprises the following steps: adding 1-2 parts of ethyl 2-methacrylate, 1.4-1.5 parts of a toughening agent, and 1-2 parts of an initiator to 14-17 parts of waterborne polyurethane, reacting at 70±5° C. for 2-3 hours to obtain a prepolymer, and finally dispersing the prepolymer with deionized water to obtain the acrylate-modified waterborne polyurethane;
[0013] Wherein, the toughening agent is preferably polyvinyl formal resin;
[0014] Wherein, the initiator is preferably 2-hydroxy-2-methyl-1-phenylpropanone.
[0015] Specifically, the preparation method of the modified epoxy vinyl ester resin comprises the following steps: mixing 0.3-0.6 parts of silicone resin with 18-21 parts of epoxy vinyl ester resin, adding 1.4-2 parts of alcohol compound, stirring evenly at 120±5°C until it becomes a paste, adding 1.4-2 parts of toughening agent and stirring evenly to obtain modified epoxy vinyl ester resin.
[0016] Wherein, the epoxy vinyl ester resin may also be one of epoxy vinyl ester resin and bisphenol A type epoxy vinyl ester resin;
[0017] Wherein, the organic silicon resin is preferably one of silicone resin or siloxane resin;
[0018] Wherein, the alcohol compound is preferably one of n-octanol, n-nonanol and n-decanol;
[0019] Wherein, the toughening agent is preferably polyvinyl butyral resin;
[0020] In the preparation process of the modified resin, in addition to the preferred toughening agents mentioned above, one or more of polyvinyl butyral resin, acrylonitrile-butadiene-styrene copolymer, ethylene-acrylate copolymer, polypropylene, polyvinyl acetal resin, polyvinyl formal resin, and polyvinyl ether-aldehyde resin can also be selected.
[0021] Furthermore, the curing agent is preferably tert-butyl perbenzoate or cumene hydroperoxide curing agent, and one or two of hydroxides, redox systems, persulfates, tert-butyl perbenzoate and tert-butyl perbenzoate can also be selected.
[0022] Furthermore, the natural flake graphite is 150-180 mesh natural flake graphite powder.
[0023] According to another aspect of the present invention, the present invention provides a method for preparing the above-mentioned high-conductivity carbon fiber composite bipolar plate base material, comprising the following steps: uniformly grinding the modified resin, curing agent and natural flake graphite, adding a conductive filler and continuing the grinding, and obtaining the high-conductivity carbon fiber composite bipolar plate base material after screening; preferably, the modified resin is one of the modified epoxy vinyl ester resins, such as modified bisphenol A epoxy vinyl ester resin.
[0024] The raw materials for the preparation of the present invention may also include 0.3-0.6 parts of organic silicon resin.
[0025] Furthermore, the organic silicon resin is preferably one of silicone resin and siloxane resin.
[0026] Furthermore, the curing agent is preferably cumene hydroperoxide curing agent.
[0027] The present invention provides a method for preparing a carbon fiber composite bipolar plate base material with high electrical conductivity comprising the above raw materials, comprising the following steps: uniformly grinding a modified resin, natural flake graphite, a curing agent and a silicone resin, adding a conductive filler for further grinding, and obtaining a carbon fiber composite bipolar plate base material with high electrical conductivity after screening; preferably, the modified resin is an acrylate-modified waterborne polyurethane.
[0028] According to another aspect of the present invention, the high conductivity carbon fiber composite bipolar plate base material of the present invention can be used to prepare ultra-thin high conductivity carbon fiber composite bipolar plates, preferably prepared by cold pressing process, comprising the following steps: placing the high conductivity carbon fiber composite bipolar plate base material in a mold, cold pressing and forming it in a hydraulic press at a pressure of 80-100MPa to obtain an ultra-thin high conductivity carbon fiber composite bipolar plate. This process can achieve direct demoulding without a release agent, and can obtain an ultra-thin composite bipolar plate.
[0029] The beneficial effects of the present invention are:
[0030] The present invention utilizes polyaniline-coated oxidized modified carbon fiber as the basic conductive filler of the bipolar plate, which can significantly increase the conductivity of the bipolar plate and effectively improve its strength; the modified resin used has better performance than the unmodified resin, and has better toughness, corrosion resistance and heat resistance. The modified resin can increase the composite elongation of the material, reduce the thickness of the bipolar plate, and improve various mechanical properties; the present invention adopts cold pressing to mold the bipolar plate base material to obtain a bipolar plate with both ultra-thinness and high conductivity, while reducing its production cost, which is expected to promote the commercial application and promotion of bipolar plates. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 : Bending strength test diagram of Examples 1-6 of the present invention.
[0032] Figure 2 : Thickness test diagram of Examples 1-6 of the present invention.
[0033] Figure 3 : Conductivity test diagram of Examples 1-6 of the present invention.
[0034] Figure 4 : Contact resistance test diagram of embodiments 1-6 of the present invention.
[0035] Figure 5 : Hydrogen permeability test diagram of Examples 1-6 of the present invention.
[0036] Figure 6 : Corrosion current density test diagram of Examples 1-6 of the present invention.
[0037] Figure 7: Surface water contact angle test diagram of Examples 1-6 of the present invention. DETAILED DESCRIPTION
[0038] The specific implementation modes of the present invention are explained in detail below. Unless otherwise defined, all technical terms and scientific terms used herein have the same meanings as those commonly understood by technicians in the technical field of the present application. Non-creative improvements made by those skilled in the art without violating the connotation of the present invention belong to the protection scope of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0039] Embodiment 1:
[0040] As a preferred embodiment of the present invention, the high conductivity carbon fiber composite bipolar plate base material used in this embodiment is prepared from the following components calculated by mass: 7.2 parts of liquid-phase oxidation-treated carbon fiber coated with polyaniline, 18.5 parts of acrylate-modified waterborne polyurethane, 72 parts of 150-180 mesh natural flake graphite powder, 0.3 parts of silicone resin, and 2 parts of cumene hydroperoxide;
[0041] Specifically, the steps for preparing the polyaniline-coated liquid-phase oxidized carbon fiber are as follows:
[0042] Calculated by mass, 0.6 parts of 10wt% potassium chlorate solution and 4 parts of carbon fiber were uniformly stirred and reacted at 80°C for 1 hour, during which a violent redox reaction occurred. After oxidation, the carbon fiber was washed with deionized water until neutral, cooled and filtered, and then placed in a drying oven at 80°C for drying to obtain carbon fiber after liquid phase oxidation treatment.
[0043] 0.3 parts of hydrochloric acid (1 mol / L), 2 parts of polyaniline solution (0.5 mol / L) and the carbon fiber after the liquid phase oxidation treatment are added to a beaker in sequence, and the temperature is controlled at 0°C and stirred in a water bath, and then 90 ml of ammonium persulfate solution is added dropwise to make the total volume of the reaction system 300 ml. After 6 hours of reaction, the color changes from transparent to blue-black, and stirring is stopped. After filtering, it is rinsed with dilute hydrochloric acid and distilled water, and the solid is dried to obtain 7.2 parts of polyaniline-coated oxidized carbon fiber;
[0044] Specifically, the preparation steps of the acrylate-modified waterborne polyurethane are as follows:
[0045] 2 parts of ethyl 2-methacrylate, 1.5 parts of polyvinyl formal resin and 1 part of 2-hydroxy-2-methyl-1-phenylpropanone were added to 14 parts of waterborne polyurethane, and the mixture was reacted at 70°C for 3 hours, and then the prepolymer was dispersed by vigorously stirring with deionized water at a speed of 1500 rpm for 1 hour to obtain 18.5 parts of acrylate-modified waterborne polyurethane.
[0046] The preparation steps of the above-mentioned high conductivity carbon fiber composite bipolar plate base material are as follows:
[0047] 18.5 parts of acrylate-modified waterborne polyurethane, 72 parts of 150-180 mesh natural flake graphite powder, 0.3 parts of silicone resin and 2 parts of cumene hydroperoxide were evenly ground in a high-speed ball mill at 400 r / min, and then 7.2 parts of liquid-phase oxidized carbon fiber coated with polyaniline were added and continued to be ground for 2 hours. After sieving 3-5 times through a 300-mesh granulator, a high-conductivity carbon fiber composite bipolar plate base material was obtained.
[0048] Embodiment 2:
[0049] As a preferred embodiment of the present invention, the high conductivity carbon fiber composite bipolar plate base material used in this embodiment is prepared from the following components calculated by mass: 7 parts of liquid-phase oxidation-treated carbon fiber coated with polyaniline, 21.4 parts of acrylate-modified waterborne polyurethane, 70 parts of 150-180 mesh natural flake graphite powder, 0.6 parts of silicone resin, and 3 parts of cumene hydroperoxide;
[0050] Specifically, the steps for preparing the polyaniline-coated liquid-phase oxidized carbon fiber are as follows:
[0051] 0.4 parts of 10wt% potassium chlorate solution and 4 parts of carbon fiber were uniformly stirred and reacted at 80°C for 1 hour, during which a violent redox reaction occurred. After oxidation, the carbon fiber was washed with deionized water until neutral, cooled and filtered, and then placed in a drying oven at 80°C for drying to obtain carbon fiber after liquid phase oxidation treatment.
[0052] 0.3 parts of hydrochloric acid (1 mol / L), 2 parts of polyaniline solution (0.5 mol / L) and the carbon fiber after the liquid phase oxidation treatment are added to a beaker in sequence, and the temperature is controlled at 0°C and stirred in a water bath, and then 90 ml of ammonium persulfate solution is added dropwise to make the total volume of the reaction system 300 ml. After 6 hours of reaction, the color changes from transparent to blue-black, and stirring is stopped. After filtering, it is rinsed with dilute hydrochloric acid and distilled water, and the solid is dried to obtain 7 parts of polyaniline-coated oxidized carbon fiber;
[0053] Specifically, the preparation steps of the acrylate-modified waterborne polyurethane are as follows:
[0054] 2 parts of ethyl 2-methacrylate, 1.4 parts of polyvinyl formal resin and 1 part of 2-hydroxy-2-methyl-1-phenylpropanone were added to 17 parts of waterborne polyurethane, and the mixture was reacted at 70°C for 3 hours, and then the prepolymer was dispersed by vigorously stirring with deionized water at a speed of 1500 rpm for 1 hour to obtain 21.4 parts of acrylate-modified waterborne polyurethane.
[0055] The preparation steps of the above-mentioned high conductivity carbon fiber composite bipolar plate base material are as follows:
[0056] 21.4 parts of acrylate-modified waterborne polyurethane, 70 parts of 150-180 mesh natural flake graphite powder, 0.6 parts of silicone resin and 3 parts of cumene hydroperoxide were evenly ground in a high-speed ball mill at 400 r / min, and then 7 parts of liquid-phase oxidized carbon fiber coated with polyaniline were added and continued to be ground for 2 hours. After sieving 3-5 times through a 300-mesh granulator, a high-conductivity carbon fiber composite bipolar plate base material was obtained.
[0057] Embodiment 3:
[0058] As a preferred embodiment of the present invention, the high conductivity carbon fiber composite bipolar plate base material used in this embodiment is prepared from the following components calculated by mass: 6.8 parts of polyaniline-coated liquid-phase oxidation-treated carbon fiber, 23.8 parts of modified bisphenol A epoxy vinyl ester resin, 68 parts of 150-180 mesh natural flake graphite powder, and 1.4 parts of tert-butyl peroxybenzoate;
[0059] Specifically, the steps for preparing the polyaniline-coated liquid-phase oxidized carbon fiber are as follows:
[0060] 0.4 parts of periodic acid solution (0.02 mol / L) and 4 parts of carbon fiber were uniformly stirred and reacted at 60°C for 1 hour, during which a violent redox reaction occurred. After oxidation, the carbon fiber was washed with deionized water until neutral, cooled and filtered, and then placed in a drying oven at 80°C for drying to obtain carbon fiber after liquid phase oxidation treatment.
[0061] 0.3 parts of hydrochloric acid (1 mol / L), 2 parts of polyaniline solution (0.5 mol / L) and the carbon fiber after the liquid phase oxidation treatment are added to a beaker in sequence, and a water bath is placed to control the temperature to 0°C and stir, and then 90 ml of ammonium persulfate solution is added dropwise to make the total volume of the reaction system 300 ml. After 6 hours of reaction, the color changes from transparent to blue-black, and stirring is stopped. After filtering, it is rinsed with dilute hydrochloric acid and distilled water, and the solid is dried to obtain 6.8 parts of polyaniline-coated oxidized carbon fiber;
[0062] Specifically, the preparation steps of the modified bisphenol A epoxy vinyl ester resin are as follows:
[0063] Mix 0.4 parts of silicone resin with 20 parts of bisphenol A epoxy vinyl ester resin, then mix with 2 parts of n-nonanol, place in a magnetic stirrer, and stir evenly at 120°C until it becomes a paste. Then add 1.4 parts of polyvinyl butyral resin to toughen it, increase its surface activity and flexural strength, and stir evenly to obtain 23.8 parts of modified bisphenol A epoxy vinyl ester resin.
[0064] The preparation steps of the above-mentioned high conductivity carbon fiber composite bipolar plate base material are as follows:
[0065] 23.8 parts of modified bisphenol A epoxy vinyl ester resin, 1.4 parts of tert-butyl perbenzoate and 68 parts of 150-180 mesh natural flake graphite powder were evenly ground in a high-speed ball mill at 400 r / min, and then 6.8 parts of polyaniline-coated carbon fiber were added and continued to be ground for 2 hours. After sieving 3-5 times through a 300-mesh granulator, a high-conductivity carbon fiber composite bipolar plate base material was obtained.
[0066] Embodiment 4:
[0067] As a preferred embodiment of the present invention, the high conductivity carbon fiber composite bipolar plate base material used in this embodiment is prepared from the following components calculated by mass: 7 parts of polyaniline-coated liquid-phase oxidation-treated carbon fiber, 21.5 parts of modified bisphenol A epoxy vinyl ester resin, 70 parts of 150-180 mesh natural flake graphite powder, and 1.5 parts of tert-butyl peroxybenzoate;
[0068] Specifically, the steps for preparing the polyaniline-coated liquid-phase oxidized carbon fiber are as follows:
[0069] 0.4 parts of periodic acid solution (0.02 mol / L) and 4 parts of carbon fiber were uniformly stirred and reacted at 60°C for 1 hour, during which a violent redox reaction occurred. After oxidation, the carbon fiber was washed with deionized water until neutral, cooled and filtered, and then placed in a drying oven at 80°C for drying to obtain carbon fiber after liquid phase oxidation treatment.
[0070] 0.3 parts of hydrochloric acid (1 mol / L), 2 parts of polyaniline solution (0.5 mol / L) and the carbon fiber after the liquid phase oxidation treatment are added to a beaker in sequence, and the temperature is controlled at 0°C and stirred in a water bath, and then 90 ml of ammonium persulfate solution is added dropwise to make the total volume of the reaction system 300 ml. After 6 hours of reaction, the color changes from transparent to blue-black, and stirring is stopped. After filtering, it is rinsed with dilute hydrochloric acid and distilled water, and the solid is dried to obtain 7 parts of polyaniline-coated oxidized carbon fiber;
[0071] Specifically, the preparation steps of the modified bisphenol A epoxy vinyl ester resin are as follows:
[0072] Mix 0.4 parts of silicone resin with 18 parts of bisphenol A epoxy vinyl ester resin, then mix with 1.6 parts of n-octanol, place in a magnetic stirrer, and stir evenly at 120°C until it becomes a paste. Then add 1.5 parts of polyvinyl butyral resin to toughen it, increase its surface activity and flexural strength, and stir evenly to obtain 21.5 parts of modified bisphenol A epoxy vinyl ester resin.
[0073] The preparation steps of the above-mentioned high conductivity carbon fiber composite bipolar plate base material are as follows:
[0074] 21.5 parts of modified bisphenol A epoxy vinyl ester resin, 1.5 parts of tert-butyl perbenzoate and 70 parts of 150-180 mesh natural flake graphite powder were evenly ground in a high-speed ball mill at 400 r / min, and then 7 parts of polyaniline-coated carbon fiber were added and continued to be ground for 2 hours. After sieving 3-5 times through a 300-mesh granulator, a high-conductivity carbon fiber composite bipolar plate base material was obtained.
[0075] Embodiment 5:
[0076] As a preferred embodiment of the present invention, the high conductivity carbon fiber composite bipolar plate base material used in this embodiment is prepared from the following components calculated by mass: 6.8 parts of liquid phase oxidation treated carbon fiber coated with polyaniline, 22.7 parts of modified epoxy vinyl ester resin, 68 parts of 150-180 mesh natural flake graphite powder, and 2.5 parts of cumene hydroperoxide;
[0077] Specifically, the steps for preparing the polyaniline-coated liquid-phase oxidized carbon fiber are as follows:
[0078] 0.3 parts of acidified potassium dichromate solution (0.02 mol / L) and 4 parts of carbon fiber were uniformly stirred and reacted at 60°C for 1 hour, during which a violent redox reaction occurred. After oxidation, the carbon fiber was washed with deionized water until neutral, cooled and filtered, and then placed in a drying oven at 80°C for drying to obtain carbon fiber after liquid phase oxidation treatment.
[0079] 0.3 parts of hydrochloric acid (1 mol / L), 2 parts of polyaniline solution (0.5 mol / L) and the carbon fiber after the liquid phase oxidation treatment are added to a beaker in sequence, and a water bath is placed to control the temperature to 0°C and stir, and then 90 ml of ammonium persulfate solution is added dropwise to make the total volume of the reaction system 300 ml. After 6 hours of reaction, the color changes from transparent to blue-black, and stirring is stopped. After filtering, it is rinsed with dilute hydrochloric acid and distilled water, and the solid is dried to obtain 6.8 parts of polyaniline-coated oxidized carbon fiber;
[0080] Specifically, the preparation steps of the modified epoxy vinyl ester resin are as follows:
[0081] Mix 0.3 parts of silicone resin with 19 parts of epoxy vinyl ester resin, and then mix with 1.4 parts of n-decanol, place in a magnetic stirrer, and stir evenly at 120°C until it becomes a paste. Then add 2 parts of polyvinyl butyral resin to toughen it, increase its surface activity and flexural strength, and after stirring evenly, obtain 22.7 parts of modified epoxy vinyl ester resin.
[0082] The preparation steps of the above-mentioned high conductivity carbon fiber composite bipolar plate base material are as follows:
[0083] 22.7 parts of modified epoxy vinyl ester resin, 2.5 parts of isopropylbenzene hydroperoxide and 68 parts of 150-180 mesh natural flake graphite powder were evenly ground in a high-speed ball mill at 400 r / min, and then 6.8 parts of polyaniline-coated carbon fiber were added and continued to be ground for 2 hours. After sieving 3-5 times through a 300-mesh granulator, a high-conductivity carbon fiber composite bipolar plate base material was obtained.
[0084] Embodiment 6:
[0085] As a preferred embodiment of the present invention, the high conductivity carbon fiber composite bipolar plate base material used in this embodiment is prepared from the following components calculated by mass: 7 parts of polyaniline-coated liquid-phase oxidation-treated carbon fiber, 21.7 parts of modified epoxy vinyl ester resin, 70 parts of 150-180 mesh natural flake graphite, and 1.3 parts of cumene hydroperoxide;
[0086] Specifically, the steps for preparing the polyaniline-coated liquid-phase oxidized carbon fiber are as follows:
[0087] 0.4 parts of acidified potassium dichromate solution (2 mol / L) and 4 parts of carbon fiber were uniformly stirred and reacted at 60°C for 1 hour, during which a violent redox reaction occurred. After oxidation, the carbon fiber was washed with deionized water until neutral, cooled and filtered, and then placed in a drying oven at 80°C for drying to obtain carbon fiber after liquid phase oxidation treatment.
[0088] 0.3 parts of hydrochloric acid (1 mol / L), 2 parts of polyaniline (0.5 mol / L) and the carbon fiber after the liquid phase oxidation treatment are added to a beaker in sequence, and a water bath is placed to control the temperature to 0°C and stir, and then 90 ml of ammonium persulfate solution is added dropwise to make the total volume of the reaction system 300 ml. After 6 hours of reaction, the color changes from transparent to blue-black, and stirring is stopped. The carbon fiber is rinsed with dilute hydrochloric acid and distilled water, filtered, and dried to obtain 7 parts of polyaniline-coated oxidized carbon fiber;
[0089] Specifically, the preparation steps of the modified bisphenol A epoxy vinyl ester resin are as follows:
[0090] Mix 0.3 parts of silicone resin with 18 parts of epoxy vinyl ester resin, and then mix with 1.4 parts of n-decanol, place in a magnetic stirrer, and stir evenly at 120°C until it becomes a paste. Then add 2 parts of polyvinyl acetal resin to toughen it, increase its surface activity and flexural strength, and stir evenly to obtain 21.7 parts of modified epoxy vinyl ester resin.
[0091] The preparation steps of the above-mentioned high conductivity carbon fiber composite bipolar plate base material are as follows:
[0092] 21.7 parts of modified epoxy vinyl ester resin, 1.3 parts of isopropylbenzene hydroperoxide and 70 parts of 150-180 mesh natural flake graphite powder were evenly ground in a high-speed ball mill at 400 r / min, and then 7 parts of polyaniline-coated carbon fiber were added and continued to be ground for 2 hours. After sieving 3-5 times through a 300-mesh granulator, a high-conductivity carbon fiber composite bipolar plate base material was obtained.
[0093] Comparative Example 1:
[0094] The difference between this comparative example and Example 1 is that the comparative example uses liquid phase oxidation treated carbon fiber which is not coated with polyaniline.
[0095] Comparative Example 2:
[0096] The difference between this comparative example and Example 3 is that the comparative example uses liquid phase oxidation treated carbon fibers that are not coated with polyaniline.
[0097] Comparative Example 3:
[0098] The difference between this comparative example and Example 5 is that the comparative example uses liquid phase oxidation treated carbon fiber which is not coated with polyaniline.
[0099] The carbon fiber composite bipolar plate base materials obtained in the above-mentioned Examples 1-6 and Comparative Examples 1-3 are prepared into carbon fiber composite bipolar plates by a cold pressing process; the cold pressing process comprises the following steps: placing the carbon fiber composite bipolar plate base material in a mold, cold pressing it in a hydraulic press at a pressure of 80-100 MPa for 2 minutes, and then forming it to obtain a carbon fiber composite bipolar plate, and performing performance testing.
[0100] The test method is as follows:
[0101] a. Bending strength test: Using a WD-10D universal testing machine, the pressure head is applied evenly and without impact at a loading speed of 0.01mm / s until the specified bending degree or fracture is reached. The bending strength of the composite bipolar plate is tested using the three-point bending method, and the average value is taken after 3-5 parallel tests.
[0102] b. Thickness test: Take the test sample at six different locations, use a thickness gauge to test the thickness, and perform 3-5 parallel tests to get the average value.
[0103] c. Conductivity test: Use YY-2511 DC low resistance measuring instrument to test the conductivity, and perform 3-5 parallel tests to obtain the average value.
[0104] d. Contact resistance test: Use YY-2511 DC low resistance measuring instrument to test the contact resistance between the composite bipolar plate and the diffusion layer, and perform 3-5 parallel tests to obtain the average value.
[0105] e. Hydrogen permeability test: Use a hydrogen permeation cell to test the hydrogen permeability, and perform 3-5 parallel tests to obtain the average value.
[0106] f. Corrosion current density test: Use CHI-660D electrochemical workstation to test the corrosion current density, use standard saturated mercury-mercurous sulfate electrode as reference electrode, and conduct 3-5 parallel tests to obtain the average value.
[0107] g. Surface water contact angle test: The contact angle of static water on the sample surface was measured using the sessile drop method, and the static water contact angle was tested using a DSA100E contact angle meter.
[0108] The test results are shown in Table 1-2 below:
[0109] Table 1: Test results of Examples 1-6
[0110]
[0111]
[0112] Table 2: Comparative Examples 1-3 Test Results
[0113]
[0114] The above results show that the bipolar plate synthesized by the base materials such as vinyl resin, silicone resin, carbon fiber, etc. can reach the required level of the bipolar plate in bending strength, and the thickness can reach 0.642mm. At the same time, under the condition of reducing its thickness, it also has extremely low contact resistance, which can significantly reduce its electric energy loss, save energy, and improve its conductivity and performance, reduce its hydrogen permeability, improve its mechanical properties, and improve the corrosion resistance of the bipolar plate, which not only reduces its production cost, but also improves the basic performance of the bipolar plate, which is conducive to its use in production. The present invention uses polyaniline-coated oxidized modified carbon fiber as the basic conductive filler of the bipolar plate. Compared with oxidized modified carbon fiber, it can significantly improve the conductivity of the bipolar plate, and has the advantages of low hydrogen permeability, low thickness, high strength, excellent corrosion resistance, low resistivity, low production energy consumption, and high efficiency.
[0115] It can be understood that the above specific embodiments are all further explanations of the present invention and are not intended to limit the scope of protection of the present invention. For those skilled in the art, all other modifications and changes obtained without creative work are within the scope of protection of the present invention.
Claims
1. A high conductivity carbon fiber composite bipolar plate base material, characterized in that: The raw materials for preparation include the following components calculated by mass: 6.8-7.2 parts of conductive filler, 18.5-23.8 parts of modified resin, 68-72 parts of natural flake graphite, and 1.4-3 parts of curing agent; the conductive filler includes polyaniline-coated oxidized carbon fiber; the modified resin includes at least one of acrylate-modified waterborne polyurethane resin and modified epoxy-type vinyl ester resin.
2. The high conductivity carbon fiber composite bipolar plate base material according to claim 1, characterized in that: The oxidation treatment method of the oxidation-treated carbon fiber includes at least one of a liquid phase oxidation method, a gas phase oxidation method, and an electrochemical anodization method.
3. The high conductivity carbon fiber composite bipolar plate base material according to claim 1, characterized in that: The modified resin includes modified epoxy vinyl ester resin; 0.3-0.6 parts of silicone resin and 18-21 parts of epoxy vinyl ester resin are mixed, and then 1.4-2 parts of alcohol compound are added, and stirred evenly at 120±5°C until it becomes a paste, and 1.4-2.4 parts of toughening agent are added and stirred evenly to obtain modified epoxy vinyl ester resin.
4. The high conductivity carbon fiber composite bipolar plate base material according to claim 3, characterized in that: The alcohol compound is one of n-octanol, n-nonanol and n-decanol.
5. The high conductivity carbon fiber composite bipolar plate base material according to any one of claim 1, characterized in that: The preparation raw materials also include 0.3-0.6 parts of organic silicon resin.
6. The high conductivity carbon fiber composite bipolar plate base material according to claim 5, characterized in that: The organic silicon resin is one of silicone resin and siloxane resin.
7. A method for preparing a high-conductivity carbon fiber composite bipolar plate substrate as claimed in any one of claims 1 to 4, characterized in that: The method comprises the following steps: uniformly grinding the modified resin, the curing agent and the natural flake graphite, adding the conductive filler for further grinding, and obtaining the carbon fiber composite bipolar plate base material with high conductivity after screening.
8. A method for preparing a high-conductivity carbon fiber composite bipolar plate substrate as claimed in any one of claims 5 to 6, characterized in that: The following steps are involved: After the modified resin, natural flake graphite, curing agent and silicone resin are evenly ground, a conductive filler is added and further ground, and a carbon fiber composite bipolar plate base material with high conductivity is obtained after screening.
9. An ultra-thin high conductivity carbon fiber composite bipolar plate, characterized in that: The carbon fiber composite bipolar plate substrate is prepared from the high conductivity carbon fiber composite bipolar plate substrate according to any one of claims 1 to 6.
Citation Information
Patent Citations
Polyaniline modified carbon fiber composite material as well as preparation method and application thereof
CN112898608A
Rapid mold pressing composite graphite bipolar plate, preparation method thereof and fuel cell
CN113903937A
